Design, Synthesis and Antiproliferative Evaluation of Novel 1,2,4-Triazole/Schiff Base Hybrids with EGFR and B-RAF Inhibitory Activities - El-Sherief, Hany A.M.; Youssif, Bahaa G.M.; Abdelazeem, Ahmed H.; Abdel-Aziz, Mohamed; Abdel-Rahman, Hamdy M. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: 1,2,4-triazoles possess a broad spectrum of biological activities such as analgesic, antimicrobial, antitubercular, anti-inflammatory and antineoplastic activities. This heterocycle and their derivatives were included into a wide variety of therapeutically interesting drugs. Hence, it is of great interest to explore new 1,2,4-triazoles as cytotoxic agents targeting EGFR, B-Raf kinases. Methods: The final compounds 9a-b, 10a-b, 11a-b, 12a-b, 13a-b and 14a-f were prepared by refluxing a mixture of triazole 3a-b and 7a-d with the corresponding benzaldehyde derivatives 8a-d in absolute ethanol to afford the target final compounds in good yields. The newly synthesized triazole-containing compounds were assessed according to standard protocols for their in vitro antiproliferative activity against four human cancer cell lines including human pancreas cancer cell line (Panc-1), pancreatic carcinoma cells (PaCa-2), colon cancer cells (HT-29) and lung cancer cells (H-460) using the propidium iodide (PI) fluorescence assay. Compounds 9a and 13a were evaluated against EGFR, B-Raf and Tubulin anticancer targets. Results: Compounds 9a, 9b, 10a, 11a, 12a, 13a and 13b showed remarkable antiproliferative activity against the tested cell lines with IC50 range of 1.3-5.9μM. Compounds 9a and 13a with the least IC50 values in the anticancer screening assay were tested against three known anticancer targets including EGFR, B-Raf kinase and Tubulin. The results revealed that compound 13a showed the highest potency against B-Raf and EGFR kinases with IC50 = 0.7 and 1.9 μM, respectively. Conclusion: 1,2,4-triazoles reported herein are potent EGFR, B-Raf inhibitors. These lead compounds will be subjected to more detailed mechanistic studies.
Keywords: Tubulin and molecular docking simulation